Influence of flocculation with dry-mixing on slump flow of high-strength concrete - Sakamoto, Yasuhiro; Fukuyama, Tomoko; Kobayashi, Tomoya; Kawasaki, Yuma (Frontiers in Built Environment, 2024)
The use of high-strength concrete in construction is expected to increase, and the manufacturing technology employed to produce such concrete needs to adapt to this rise. High-strength concrete has a workability that can vary significantly depending on the mixing conditions, even with the same mix design and in the same environment. This research focuses on the change in workability due to dry-mixing (i.e., mixing of fine aggregate with cement in the early stage) in the mixing process of a high-strength concrete mix using a revolving-double paddle mixer. As a result, it was confirmed that the slump flow value difference caused by dry-mixing was about 25 cm. Furthermore, Cryo-SEM (which can observe the specimens in the frozen state) image analysis revealed that dry-mixing causes flocculation of cement particles. The amount of admixtures adsorbed was then analyzed. This study concluded that flocculation affects the degree and timing of admixture adsorption in the later stages of the mixing process, leading to differences in concrete workability.